Non-employment and changes in smoking, drinking, and body weight. Issue 6826 (29th February 1992) - Morris, J. K.; Cook, D. G.; Shaper, A. G.
Abstract : OBJECTIVE--To assess the effect of unemployment and early retirement on cigarette smoking, alcohol consumption, and body weight in middle aged British men. DESIGN--Prospective cohort study (British regional heart study). SETTING--One general practice in 24 towns in Britain. SUBJECTS--6057 men aged 40-59 who had been continuously employed for five years before the initial screening. Five years after screening 4412 men had been continuously employed and 1645 had experienced some unemployment or retired. MAIN OUTCOME MEASURES--Numbers of cigarettes smoked and units of alcohol consumed per week and body mass index (kg/m2). RESULTS--An initial screening significantly higher percentages of men who subsequently experienced non-employment smoked or had high alcohol consumption than of men who remained continuously employed: 43.0% versus 37.0% continuously employed for cigarette smoking (95% confidence interval for difference 3.2% to 9.0%) and 12.1% versus 9.0% for heavy drinking (1.3% to 5.1%). There was no evidence that men increased their smoking or drinking on becoming non-employed. Men non-employed through illness were significantly more likely to reduce their smoking and drinking than men who remained continuously employed. Men who experienced non-employment were significantly more likely to gain over 10% in weight than men who remained continuously employed: 7.5% versus 5.0% continuously employed (0.9% to 4.0%). CONCLUSIONS--Loss of employment was not associated with increased smoking or drinking but was associated with an increased likelihood of gaining weight. The long term effects of the higher levels of smoking and alcohol consumption before nonemployment should be taken into account when comparing mortality and morbidity in groups of unemployed and employed people.